Model spodbujanja rezilientnosti v šolskem okolju - Kiswarday, Vanja (Revija za elementarno izobraževanje, 2014)
A Model of Fostering Resilience in School Context. Resiliency theory examines the factors that increase the efficiency of the individual to overcome the obstacles that in adolescence are associated with schooling. Promoting the development of resiliency is the most effective when conducted directly through experiential learning. Literature highlights an inclusive, safe and sound learning environment that sets high but realistic expectations, provides assistance and support to develop lifelong competences, and allows an independent and active participation as key factors. These factors are also highlighted by the modern didactic and methodical principles, so we were interested in the extent to which at school resiliency is promoted by Slovenian teachers, although not being familiar with the theory of resiliency. We designed a model to promote resiliency in the school environment and evaluated it on a sample of 429 teachers of different professional profiles.
Keywords: resilience; protective factors; risk factors; school; didactical and methodical principles; teachers’ professional profile